THE EFFECT OF THE COVID 19 VIRUS AND ONLINE LEARNING ON ENGLISH SUBJECTS IN SENIOR HIGH SCHOOL - Susan Rachmawati; Upik Djaniar; Arman Syah Putra; Nurul Aisyah (Journal of Innovation Research and Knowledge, 2021)
The background of this research is to find out the effect of the covid-19 virus and variables related to English subject matter and online learning systems in high schools. With the variables above, can these variables affect the teaching and learning system in senior high school. This study uses quantitative methods which are considered appropriate in this study because by using the survey method and conducting questionnaires to 100 people who were randomly selected by the survey, it can produce valid data and can be used for future research. The problem raised in this study is how to find out the effects of the covid 19 pandemic, even though the effects of the covid 19 pandemic are felt in all fields. This research is only limited to the field of education, especially high school education. and can know the effects of the covid 19 pandemic. this study produces new data that can find out the effects of the covid 19 pandemic on the world of education, especially in high school in English subjects, with the results of this research can produce data that can be used as references and future research.